WOMEN STORIES OF THE VIOLENT CONFLICT IN POSO AND TRAUMA HEALING - Subagya, Yustinus Tri (Sanata Dharma University, 2018)
This article intends to unfold woman experiences in coping with trauma of the violent conflict and their efforts to release its burden. In the last decade, the victims of violence are referred to get a psycho-theuraphy of trauma due to their depression from the disaster. Development agencies often initiate the program of trauma healings for the victims with the post traumatic stress disorder (PTSD) model, especially for women who were described as passive actors and became the most vulnerable victims in the violent conflict. The fact that women involved in the conflict as active social actors was less accounted due to the healing mechanism. Their experiences such as individual memories on vengeance and strugling for family survival Â tend to be inarticulated, except their attempts to forget of the trumatic burdens. This article defines the articulation of women stories as both a crucial factor in healing their past traumatic experiences which in turn the stories could be as an effective approach to pave a way for reconciliation. We use stories of women experiences in Poso, Indonesia as the lesson. The contribution of narrative for releasing the burden of traumatic experiences from the past atrocities has been the subject of the recent discussion in academic fields such as Anthropology or Psychology as well as Humanitarian Agencies or Development Practitioners. Â DOI:Â https://doi.org/10.24071/ijhs.2018.020111